1944
DOI: 10.1172/jci101516
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Clinical, and Immunological Studies on the Products of Human Plasma Fractionation. Ix. The Treatment of Shock With Concentrated Human Serum Albumin: A Preliminary Report 12

Abstract: We have had the opportunity to treat 6 patients in shock with concentrated human serum albumin, prepared from pooled normal human plasma by the method of Cohn and co-workers (1).3 Five of these patients had circulatory failure from hemorrhage and the sixth from extensive burns. These observations were made at the beginning of our experience with the technics utilized in the study of shock by Cournand and co-workers (3). At this time, routine determinations of the cardiac output before and after therapy were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1944
1944
1974
1974

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…An average water retention capability of 17.4 ml per g albumin was determined. This figure was confirmed shortly afterwards by WARREN and his co-workers [1485]. Mild variations in the state of hydration did not affect these findings (dehydration 15 hours before to 20 hours after addition of the albumin compared with additional oral water and salt administration during the experiment).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…An average water retention capability of 17.4 ml per g albumin was determined. This figure was confirmed shortly afterwards by WARREN and his co-workers [1485]. Mild variations in the state of hydration did not affect these findings (dehydration 15 hours before to 20 hours after addition of the albumin compared with additional oral water and salt administration during the experiment).…”
supporting
confidence: 56%
“…WARREN et al [1485] have shown the effectivity of the albumin therapy by means of careful circulatory analysis. Blood pressure and cardiac output rise, and the arterio-venous oxygen difference decreases.…”
Section: Therapeutic Resultsmentioning
confidence: 99%
“…However, small amounts of albumin subsequently have been allocated to two groups of investigators, whose detailed studies of selected shock cases might contribute information of value to the armed forces. The results of these investigations are presented in subsequent papers in this series (7,8). The results in the original group of 200 cases have been previously reported (9).…”
Section: Introductionmentioning
confidence: 74%
“…Clinical evaluation The experimental evidence cited above seemed to confirm so well the anticipated theoretical advantages of concentrated albumin that a dinical program was instituted to determine whether the value of albumin could be proved in a series of actual cases of shock. To get a rapid, impartial evaluation, the cooperation of a number of clinics 8 was obtained, and their results were submitted to us for study. At the outset, it was felt that 1000 cases of shock of various types should be treated for the proper evaluation of this material.…”
Section: Introductionmentioning
confidence: 99%
“…(Submitted for publication November 18, 1949; accepted, December 5,1949) Human serum albumin for therapeutic use was made available during the war and was used chiefly in the treatment of shock because of its high osmotic properties (1)(2)(3). Its use in kidney and liver disease as a nutrient material was also investigated (1,4,5).…”
mentioning
confidence: 99%